(3GdJShjb hGdecGfI GdPgfjI (B:s (3efXhQ ESJQGJjLj (B/s - (3GdYRGhj, eMeO YHO GdhgGH eMeOs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2012)
(3fXQI TehdjI deaghe GdJShjb GdMOjK hGdJbSje GdShbj hJMOjO GdgOa GdShbj, GdHjFI GdJShjbjI, ESJQGJjLjI JWhjQ GdefJLGJ GdLOjOI , Sdhc GdRHhf, ESJQGJjLjI GdecGfI GdPgfjI(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs